Avoiding Equivalent Test Executions in Software Product Line Testing - Pilsu Jung; Jaeho Kim (IEEE Access)
In the context of software product line (SPL), test cases are reused for testing of multiple products that have commonality. In such a case, their executions may contain repetitions of equivalent executions, which are the test executions that have the identical execution flow and produce the same testing result. In SPL testing, repeating equivalent test executions should be avoided because it does not contribute to finding new faults and unnecessarily increases the SPL testing cost. This paper defines two types of equivalent test executions and points out that equivalent test executions increase the test redundancy. To show how equivalent test executions occur in a product line, we conduct a preliminary experiment using the VendingMachine SPL and its evolved versions. Then we propose a method to reduce the test redundancy of SPL by avoiding repetition of equivalent test executions. Our experimental evaluation with two SPL systems shows that our proposed method reduces the number of test executions by 57.1% on average compared to the exhaustive execution method without sacrificing fault detection effect.